2021
DOI: 10.1002/qj.3959
|View full text |Cite
|
Sign up to set email alerts
|

Scaling characteristics of modelled tropical oceanic rain clusters

Abstract: The scaling exponents of the distributions of cluster rain amount, R, and cluster size, A, for oceanic rain clusters over the Indian and Pacific warm pools, and the intertropical convergence zones over the eastern Pacific and the tropical Atlantic, were obtained from a set of regional climate model downscaling products. The main aim of the investigation is to compare the model cluster's scaling characteristics with those obtained from observations that have been reported previously. The scaling exponents for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…The scheme improved the representation of model cloudiness and reduced the positive bias of surface radiation fluxes compared to observed data and reanalysis. The scheme, which considers the interaction of deep convective clouds and radiation, was used in a study with different time scales on the tropical belt at high resolution (Fonseca et al, 2019) and more recently on tropical ocean precipitation cores (Teo et al, 2021). Teo et al (2021) showed that by using the scheme proposed by Koh and Fonseca, the WRF model better simulated the climatological circulation, precipitation, surface radiative fluxes, 2-m temperature, and soil moisture of four monsoon seasons in tropical regions of intense deep convection activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The scheme improved the representation of model cloudiness and reduced the positive bias of surface radiation fluxes compared to observed data and reanalysis. The scheme, which considers the interaction of deep convective clouds and radiation, was used in a study with different time scales on the tropical belt at high resolution (Fonseca et al, 2019) and more recently on tropical ocean precipitation cores (Teo et al, 2021). Teo et al (2021) showed that by using the scheme proposed by Koh and Fonseca, the WRF model better simulated the climatological circulation, precipitation, surface radiative fluxes, 2-m temperature, and soil moisture of four monsoon seasons in tropical regions of intense deep convection activity.…”
Section: Introductionmentioning
confidence: 99%
“…The scheme improved the representation of model cloudiness and reduced the positive bias of surface radiation fluxes compared to observed data and reanalysis. The scheme, which considers the interaction of deep convective clouds and radiation, was used in a study with different time scales on the tropical belt at high resolution (Fonseca et al ., 2019) and more recently on tropical ocean precipitation cores (Teo et al ., 2021). Teo et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation